Avaliação dos parâmetros que afetam o comportamento elétrico de polietileno de alta densidade aditivado com negro de fumo condutor - Boog, Jorge Henrique Faber (2025)
Ethanol and gasoline powered automotive vehicles hold a common thermoplastic part molded through injection process, the fuel tank inlet. These parts are typically produced with a polyethylene (PE) compound, and should present static dissipator behavior, avoiding accumulation of electric charges that could cause ignitions during fuel feeding. PE is an electrical insulative material and, therefore, it is necessary to fill it with electrically conductive additives, such as conductive carbon black (CCB), to electrical percolation phenomenon occur and desired electrical behavior to be reached. Electrical conductivity of the part will depend on CCB structure and its chemical composition. Matrix composition, viscosity and molding process will influence on CCB dispersion through the molded part and, as consequence, on the probability of contact between aggregates, enabling or hindering creation of an electrically conductive network. In this project, two CCB types were used as conductive fillers for PE in 10% to evaluate influence of their structures on conductivity. Influence of molding was evaluated by two different methods, injection and compression molding. TGA, DSC, PLOM, oscillatory state rheology, SEM, thermal treatments, skin removal and electrical resistivity analysis were conducted, and results confirmed influence of CCB structure and molding process as key-drivers to obtain electrically conductive parts. The lower structuration degree of CCB, associated with molecular and aggregates orientation in the skin layer resulting from the injection molding process, undermined formation of the electrical percolation network, which was not noted for compression molded parts. Polymeric matrix characteristics have shown less importance to occurrence of electrical percolation phenomenon.